Morphology of Tumours Induced in Hamsters by CELO Virus, Tumour Tissue, and Tumour Cells Grown in Culture* - Mancini, L. O. (Nature Publishing Group, 1972)
Tumours in hamsters, induced by the chicken-embryo-lethal-orphan (CELO) virus, by tumour tissue transplants, or by tumour cells grown in culture, were well circumscribed solid tumours and covered by a thin capsule-like structure. All were fibrosarcomata. However, tumours produced by the 3 inocula exhibited the following histological differences. Neoplasms induced by CELO virus were generally less differentiated and were composed of cells with polygonal or oval nuclei and indistinct cytoplasmic boundaries. Numerous multinucleated bizarre giant cells were found. Those produced by tumour tissue transplants were more differentiated and were composed of spindle shaped cells with abundant collagen fibre formation. Neoplasms induced by tumour cells grown in culture were generally undifferentiated with many mitotic figures and contained numerous giant cells. Cells from tumours induced by CELO virus or tumour transplants produced similar morphologies when cultured in vitro. The cell cultures consisted of large cells with oval or rounded large nuclei and prominent nucleoli. Multinucleated giant cells, cells in mitosis, and a disorganized growth pattern were also characteristic of the cell cultures. However, mitosis and a piling-up of cells occurred more frequently with cell cultures derived from the CELO virus-induced tumour. IMAGES: